Novel transition metal-free synthetic protocols toward the construction of 2,3-dihydrobenzofurans: a recent update - Mushtaq, Aqsa; Irfan, Muhammad; Haq, Atta ul; Mansha, Asim; Khan, Samreen Gul; Zahoor, Ameer Fawad; Parveen, Bushra; Irfan, Ali; Kotwica-Mojzych, Katarzyna; Glowacka, Mariola; Mojzych, Mariusz (Frontiers in Chemistry, 2024)
2,3-Dihydrobenzofurans are noteworthy scaffolds in organic and medicinal chemistry, constituting the structural framework of many of the varied medicinally active organic compounds. Moreover, a diverse variety of biologically potent natural products also contain this heterocyclic nucleus. Reflecting on the wide biological substantiality of dihydrobenzofurans, several innovative and facile synthetic developments are evolving to achieve these heterocycles. This review summarizes the transition-metal-free, efficient, and novel synthetic pathways toward constructing the dihydrobenzofuran nucleus established after 2020.